The Innovative Cities – A Modern Concept for Their Development - Chobanova, Rositsa (Research Papers, 2018)
The paper attempts to contribute to a better understanding the concept for innovative cities as a concept for territorial development in the era of accelerated technology change and urbanization. In this respect the main policy challenge at both European and national level is development of a new paradigm in support of the policy design at the level of city governance Based on analysis it characterizes innovativeness as a function of  government of a city, trying to identify its grassroots and specifics. Along with this, in the paper are summarized conditions for innovative cities creation and development. Four visions for innovative development of cities are presented as well as stages of such development. The study ends with summarizing of the main author?s conclusions and recommendations for modern innovative city management.
Keywords: Urbanization; Technological change; Development strategies; Innovations